2019
DOI: 10.1002/nur.21943
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychological distress in low‐income mothers over the first postpartum year

Abstract: Up to 25% of postpartum women experience psychological distress including stress, depressive, or anxiety symptoms during the postpartum period. The purpose of this study was to explore the extent to which social determinants of health and allostatic load score, a 10‐item index of biologic measures of chronic stress, predict psychological distress in low‐income pregnant women over the first postpartum year. We conducted a secondary data analysis of the Child Community Health Research Network data set. The psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The tandem presence of anxiety in postpartum women with OUD has been previously reported 8,26 ; however, the associated of mental health issues and fear of being reported to child protective services warrants further exploration. Previous research finding suggests that psychological distress induced by a modifiable risk factor in the first year postpartum can be lessened by providing targeted interventions designed to minimize the effects of a trigger and decrease the burden of a negative outcome 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tandem presence of anxiety in postpartum women with OUD has been previously reported 8,26 ; however, the associated of mental health issues and fear of being reported to child protective services warrants further exploration. Previous research finding suggests that psychological distress induced by a modifiable risk factor in the first year postpartum can be lessened by providing targeted interventions designed to minimize the effects of a trigger and decrease the burden of a negative outcome 11 …”
Section: Discussionmentioning
confidence: 99%
“…For childbearing women with OUD, the postpartum period represents a time of increased vulnerabilities. In addition to the need for a woman's physical recovery, adaption to parenthood, and learning how to breastfeed, 7 postpartum women with OUD have an elevated risk of being diagnosed with a behavioral health disorder (depression, anxiety), 8 intimate partner violence (IPV), 9,10 social adversity (poverty, food insecurity), 11 or substance use relapse 12 . In fact, women with OUD overdose more frequently in the postpartum period when compared with pregnancy; the highest rate occurring at 7 to 12 months postpartum 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed a significant association be tween depressive and anxiety symptoms and allostatic Psychother Psychosom 2021;90:11-27 DOI: 10.1159/000510696 load [279][280][281][282][283], not confirmed by others [233,[284][285][286]. In the association between childhood physical abuse and depression in adulthood, allostatic load appeared to have a mediating role [287].…”
Section: Mood and Anxiety Disordersmentioning
confidence: 98%
“…In total, 64% of mothers in our sample reported depression or anxiety and this was not associated with wheeze. Identifying the prevalence of prenatal depression and anxiety nationally is challenging, although the evidence suggests that approximately 25% of women report psychological distress including depression or anxiety during pregnancy [ 17 ]. A relationship between depression and anxiety and wheeze may have been washed out due to the high prevalence of depression and anxiety in this sample or bias in self-reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting just 1–2 life stressors increased the probability of smoking by 6% relative to reporting no life stressors [ 16 ]. In general, women with low income and low educational attainment are at increased risk for reporting perinatal stressful life events, psychological stress and correlates of stress, and depression and anxiety [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%